Can stigma become a resource? The mobilisation of aesthetic–corporal capital by female immigrant entrepreneurs from Brazil - Malheiros, J.; Padilla, B. (Identities: Global Studies in Culture and Power, 2015)
The proportion and visibility of Brazilian women and particularly the specific images of Brazil and Brazilians in the Portuguese imaginary have contributed to the construction of new versions of stigma and stereotypes surrounding them. Mainstream images of Brazilian women have incorporated prejudices about the sensuality of Creole women who are reminiscent of the Portuguese colonial imaginary. Starting from this stigmatised image, we show how Brazilian women entrepreneurs in the beauty' business filiere reinterpret and mobilise this perceived negative image, transforming it into an added value associated with an aesthetic' Brazilian body culture. This idea of body' aesthetics becomes a business resource transformed into aesthetic-corporal capital, a key component of the Brazilian beauty business filiere. Empirically, this research is based on qualitative elements, in particular 25 interviews with Brazilian women entrepreneurs of the beauty filiere working in Portugal, collected for the project BELTS-W (Brazilian Entrepreneurial Links and Transnational Strategies - Women).